2012
DOI: 10.1007/s00167-012-2199-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of the side-cutting manoeuvre associated with ACL injury in young female handball players

Abstract: Diagnostic studies, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 21 publications
0
66
0
Order By: Relevance
“…In addition, to effectively change momentum as rapidly as possible, athletes rotate their trunk towards the desired direction of travel prior to the COD step [73]. This rotation may explain the high peak muscle activity of the adductor longus in the COD, as the adductors function as stabilizers of the hip in CODs [54,74]. To change momentum, the athletes need to decelerate by maximizing ground contact time whereby the muscles eccentrically decelerate joint movements [75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, to effectively change momentum as rapidly as possible, athletes rotate their trunk towards the desired direction of travel prior to the COD step [73]. This rotation may explain the high peak muscle activity of the adductor longus in the COD, as the adductors function as stabilizers of the hip in CODs [54,74]. To change momentum, the athletes need to decelerate by maximizing ground contact time whereby the muscles eccentrically decelerate joint movements [75].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies found inconsistent relationships between countermovement-jump and COD performance [11,[46][47][48][49][50], varying by the tests assessed. Although electromyography (EMG) measurements have been assessed in COD [51][52][53][54] and countermovement-jumps [55,56], to the best of the authors knowledge, no earlier research has applied EMG when investigating the relationship of countermovement-jumps and COD. A high muscle peak activity is an indicator of muscular effort made during a particular action [57].…”
Section: Introductionmentioning
confidence: 99%
“…The standardised side cutting movement was performed with instructions to the participants to perform the movement as fast and forcefully as possible, to best simulate the conditions of match play 11 16. An 8 camera Vicon 612 system (Oxford, England), and an AMTI force plate (Massachusetts, USA) were used to evaluate the side cutting movement with a procedure previously described 17. The knee joint valgus angle at IC as well as maximal knee joint valgus moment during the side cutting movement was calculated for the preferred push-off leg, using the Vicon Plug-in-Gait software module.…”
Section: Methodsmentioning
confidence: 99%
“…Leg dominance was defined as the leg the athletes would use if they were required to push off the ground and then throw a ball, as previously described in handball (Bencke et al, 2013). The IU provides the linear acceleration and angular displacement orientation values in a sensor-fixed Cartesian reference frame (XYZ).…”
Section: Methodsmentioning
confidence: 99%